Clinical Holistic Medicine: Pilot Study on the Effect of Vaginal Acupressure (Hippocratic Pelvic Massage) - Søren Ventegodt; Birgitte Clausen; Joav Merrick (The Scientific World Journal)
This is a pilot study of 20 female patients with a long history of sexual problems (mean is 8.92 years) who received vaginal acupressure (VA) with a quantitative and qualitative evaluation: 56% experienced help and none reported setbacks, 89% rated the treatment to be of high quality, and 89% rated it as valuable. After the treatment, most reported their problems to be less serious and their general quality of life improved. Only 17% reported minor or temporary side effects. VA was found statistically and clinically significant (p < 0.05, improvement more than 0.5 step on a 5-point Likert scale) to help patients with chronic genital pains, pain or discomfort during sexual intercourse, lack of desire or orgasm, and subjective sexual insufficiency, and all patients taken as one group (about 1 step up a 5-point Likert scale). Self-evaluated physical and mental health was significantly improved for the total group; the relationship with partner, the subjective sexual ability, and the quality of life that were measured with QOL1 and QOL5 questionnaires were all significantly improved. VA or Hippocratic pelvic massage is technically a simple procedure corresponding to the explorative phase of the standard pelvic examination, supplemented with the patient’s report on the feelings provoked followed by processing and integration of these feelings, but ethical aspects are complicated. Acupressure through the vagina/pelvic massage must be done according to the highest ethical standard with great care, after obtaining consent and the necessary trust of the patient within the framework of the local laws. It must be followed by conversational therapy and further holistic existential processing.